ENT300 Lejen Printing Service / Abdul Hazeeq Fikhri Abdul Rahman... [et.al] - Abdul Rahman, Abdul Hazeeq Fikhri; Reyfill Konnik, Ambrose Samuel; Durasad, Ariffin Mirza; Ahmad, Muhammad Mikhail; Abdul Aziz, Nazmi Naqiuddin; Apui, Brandon (2015)
This business is based on partnership where it consists of six (6) members which hold important positions in the company such as General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is printing service. We had agreed Abdul Hazeeq Fikhri Bin Abdul Rahman is our General Manager, Ambrose Samuel Anak Reyfill Konnik as Marketing Manager, Ariffin Mirza Bin Durasad and Muhammad Mikhail Bin Ahmad as Operating Manager, Nazmj Naqiuddin Bin Abdul Aziz as Administration Manager and Brandon Apui as Financial Manager- The selection of manager is based experiences, skills and ability. Lejen Printing Service is a business that provides printing service to the customers in area of UiTM Samarahan 2, 94300 Kota Samarahan Sarawak. Lejen Printing Service is located at Lot RN 10 Jalan Meranek, UiTM Samarahan 2, 94300 Kota Samarahan Sarawak This business will start to operate on 4th January 2016. To make it more attractive and interesting, we decided to create our own application for our printing service which is called 'Lejen Print'(can be found in Google Playstore) that the customer can download and use our application to send their documents to us so we can print their documents before they arrive to collect it The initial capital for Lejen Printing Service is RM 35,444. The business is targeting total combined profits of RM 137,215 by the end of three years. With loan given as a support from MayBank Berhad, we are hoping and wishing to make Lejen Printing Service able to achieve outstanding demand from consumer. Our business is expected to commence on 2016 and our vision is to make our business a well-known, established and satisfied by our customers. This will be realized by the full cooperation and efforts among the partners to promote business. We will expect that our business will become more developed in the near future because with the new innovation in our printing service, the demand will increase. This will give more advantages for us to make our service more profitable and stable in the long run.